1995
DOI: 10.1128/mcb.15.3.1220
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Activator GCN4 Contains Multiple Activation Domains That Are Critically Dependent on Hydrophobic Amino Acids

Abstract: GCN4 is a transcriptional activator in the bZIP family that regulates amino acid biosynthetic genes in the yeast Saccharomyces cerevisiae. Previous work suggested that the principal activation domain of GCN4 is a highly acidic segment of approximately 40 amino acids located in the center of the protein. We conducted a mutational analysis of GCN4 with a single-copy allele expressed under the control of the native promoter and translational control elements. Our results indicate that GCN4 contains two activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
193
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(210 citation statements)
references
References 53 publications
16
193
1
Order By: Relevance
“…Thus, although Gcn4 appears to make multiple, low affinity interactions with several Gal11 regions, Pdr1 and Oaf1 interact more tightly, and perhaps exclusively, with the KIX domain. This view is consistent with our previous finding that the Gcn4 activation domain has a random coil structure in solution (63) and contains seven different clusters of hydrophobic residues scattered throughout the acidic activation domain, whose functions in Gcn4-Mediator interactions and transcriptional activation are highly redundant (47,61,62).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, although Gcn4 appears to make multiple, low affinity interactions with several Gal11 regions, Pdr1 and Oaf1 interact more tightly, and perhaps exclusively, with the KIX domain. This view is consistent with our previous finding that the Gcn4 activation domain has a random coil structure in solution (63) and contains seven different clusters of hydrophobic residues scattered throughout the acidic activation domain, whose functions in Gcn4-Mediator interactions and transcriptional activation are highly redundant (47,61,62).…”
Section: Discussionsupporting
confidence: 81%
“…Supporting the conclusion that Gal11 contains independently functioning interaction modules, we found that distinct recombinant Gal11 polypeptides containing the KIX domain, a region altered by ⌬5 and the WQV substitution, and a region encompassing ⌬8 all bind to recombinant Gcn4 in vitro in a manner enhanced by the hydrophobic residues in Gcn4 necessary for Mediator binding to Gcn4 in vitro and transcriptional activation by Gcn4 in vivo (47,61,62). Furthermore, we used NMR chemical shift mapping to provide evidence that the recombinant Gcn4 activation domain interacts specifically with the KIX domain in solution, contacting a surface that overlaps with, but is distinct from, surfaces contacted by segments of other yeast or mammalian activation domains.…”
Section: Discussionmentioning
confidence: 51%
“…The transcription of the HIS4 gene is known to be upregulated by Gcn4p under conditions of amino acid starvation (Drysdale et al 1995). We thus determined whether Gcn4p induced by CPZ increases the -galactosidase activity in cells containing the HIS4-lacZ reporter.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of particular transcriptional activators has sometimes revealed the presence of multiple activation domains within a single activator protein (Ma and Ptashne, 1987;Courey and Tjian, 1988;Goodrich et al, 1993;Tanaka and Herr, 1994;Drysdale et al, 1995). In certain of these cases, activation domains have been demonstrated to consist of minimal activation modules which, when reiterated, result in a synergistic activation of transcription (Tanaka and Herr, 1994;Blair et al, 1996), but the meaning of this observation has not been clear.…”
Section: Introductionmentioning
confidence: 99%